Changing methodology results in operational drift in the meaning of leaf area index, necessitating implementation of foliage layer index - Rapson GL (John Wiley and Sons Ltd, 2018)
Leaf area index (LAI) was developed to describe the number of layers of foliage in a monoculture. Subsequent expansion into measurement by remote-sensing methods has resulted in misrepresentation of LAI. The new name foliage layer index (FLI) is applied to a more simply estimated version of Goodall's "cover repetition," that is, the number of layers of foliage a single species has, either within a community or in monoculture. The relationship of FLI with cover is demonstrated in model communities, and some potential relationships between FLI and species' habit are suggested. FLIcomm is a new formulation for the number of layers of foliage in a mixed-species' community. LAI should now be reserved for remote-sensing applications in mixed communities, where it is probably a nonlinear measure of the density of light-absorbing pigments.
Keywords: agriculture; chlorophyll; cover repetition; growth analysis; leaf area; shade‐light